Hubungan Antara Interaksi Teman Sebaya Dengan Penyesuaian Sosial Pada Siswa - Adalat A, Agam; , Usmi Karyani, S.Psi, M.Si (2015)
ABSTRACT This research aims to know the relationship between peer interactions with social adjustments on students. The hypothesis put forward by researchers i.e. There is a positive relationship between peer interactions with social adjustments on students. Research methods used in this research is quantitative methods with the total number of respondents as much as 118 people. Measuring instrument used in this research is peer interaction scale totalling 29 aitem and scale social adjustments totalling 32 aitem. Technique of data analysis used in this study was correlation product moment. Based on the results of the analysis of the data obtained correlation coefficient (r) of 0,523; p = 0.000 (p < 0.01), so the hypothesis proposed is accepted. It means that there is a very significant positive relationship between peer interactions with social adjustment. Effective contribution between peer interactions with social adjustment indicates that the determinant of the coefficient (r2) of variable interaction, so 0,273 peers contribute effectively amounted to 27.3%, in influencing the social adjustment in students, while the rest was 72,7% influenced by other variables outside of peer interaction. Key Words: Interaction, Peers, Students, Social Adjustment